REDEFINING THE FUTURE OF TALENT ACQUISITION: THE GENESIS OF IMMERSIVE VR RESUMES THROUGH DESIGN THINKING - Airul Shazwan Norshahimi; Sharunizam Shari; Hamwira Sakti Yaacob; Siti Aqilah Yop, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The rapid evolution of virtual reality (VR) technology is poised to revolutionize the professional recruitment landscape, shifting the paradigm from the linearity and static nature of traditional resumes to immersive VR resumes. This article introduces a groundbreaking framework anchored in the Design Thinking process model, which offers a structured, user-centric approach to creating VR resumes on platforms like Spatial. Rooted in five stages—Empathise, Define, Ideate, Prototype, and Test—this methodology emphasizes the importance of user experience, iterative design, and context. By seamlessly integrating 'context' and 'form', the proposed strategy aids professionals in designing resonant and interactive resumes in a virtual space. The application of VR in Spatial offers features like customizable 3D environments, personalized avatars, and real-time collaborations, empowering candidates to craft compelling narratives of their professional journeys. Although industries like technology and design are predicted to be early adopters, the adoption of VR resumes might encounter initial resistance due to factors like a lack of standardization and concerns over inclusivity. However, with potential integrations on platforms like LinkedIn and the prospect of virtual job fairs, VR resumes have the potential to redefine engagement methods in recruitment. As the professional world grapples with this transformation, it's vital to strike a balance, ensuring that VR resumes complement rather than replace traditional methods, fostering a recruitment process that is technologically advanced yet deeply human-centric and inclusive.